2018
DOI: 10.1002/ceas.12095
|View full text |Cite
|
Sign up to set email alerts
|

Multicultural Personality and Multicultural Counseling Competency in Counselor Trainees

Abstract: The authors hypothesized that multicultural personality and ethnic identity would significantly predict variance in multicultural counseling competencies in counselor trainees, beyond the variance predicted by demographics, multicultural training, openness, and cognitive racial attitudes. Results showed multicultural personality predicted multicultural counseling competency, but ethnic identity did not. Results and implications are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 45 publications
2
15
0
1
Order By: Relevance
“…Third, given the relationship between multicultural personality scores and counselor trainees' levels of self-reported multicultural counseling competence (Fietzer et al, 2018), counseling program admission's committees may want to attend more to personal variables in admissions reviews and interviews. Fourth, for beginning counselor trainees, completing and processing scores on the MPI-SF might prove fruitful in terms of developing self-awareness around multicultural issues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, given the relationship between multicultural personality scores and counselor trainees' levels of self-reported multicultural counseling competence (Fietzer et al, 2018), counseling program admission's committees may want to attend more to personal variables in admissions reviews and interviews. Fourth, for beginning counselor trainees, completing and processing scores on the MPI-SF might prove fruitful in terms of developing self-awareness around multicultural issues.…”
Section: Discussionmentioning
confidence: 99%
“…Scores derived from the factors reached satisfactory levels of internal consistency, were not redundant with one another, correlated with convergent variables as predicted, and demonstrated evidence of incremental validity in predicting a host of criterion variables beyond the variance accounted for by broad personality measures (i.e., the Five-Factor Model). Further, there is evidence that the hygiology model predicts the altruistic behavior of individuals in economic game theory beyond that of broad personality traits (Fietzer et al, 2016), predicts allophilic attitudes toward Asian Americans (Korol, Fietzer, & Ponterotto, 2018), and predicts multicultural counseling skills (Fietzer, Mitchell, & Ponterotto, 2018). However, one concern with the MPI is that it is a long instrument containing 70 items that risks respondent fatigue, particularly when completed in a study with other measures.…”
mentioning
confidence: 99%
“…Diversity and inclusion were central to this theme, and investigations were primarily qualitative, although several were quantitative. Research on master’s‐level students found that age, political, spiritual, and religious factors predicted perceived psychological safety and appreciation of differences (Giordano, Bevly, Tucker, & Prosek, 2018); multicultural personality, not ethnic identity, predicted multicultural counseling competency (Fietzer, Mitchell, & Ponterotto, 2018); and helping professionals from different fields did not vary in need for social distance from mental illness (Tillman et al, 2018). Qualitative investigations included those on men’s experiences (Crockett, Elghoroury, Popiolek, & Wummel, 2018) and microaggressions toward lesbian, gay, bisexual, transgender, queer or questioning, plus other identities (LGBTQ+) students (Bryan, 2018) in master’s degree programs.…”
Section: Understanding Stakeholdersmentioning
confidence: 99%
“…Role theory constitutes the theoretical background of the concept of multicultural personality (Van Oudenhoven & Van der Zee, 2002). The theory focuses on the dimensions of human characteristics to explain the behavioral aspects of multicultural personality traits (Fietzer, Mitchell, & Ponterotto, 2018). Many studies attempted to explain multicultural personality traits (Ponterotto, 2010).…”
Section: Multicultural Personality Traitsmentioning
confidence: 99%